2016
DOI: 10.5194/tc-2016-234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ground surface temperatures indicate the presence of permafrost in North Africa (Djebel Toubkal, High Atlas, Morocco)

Abstract: Abstract. Relict and present-day periglacial activity have been reported in the literature for the upper reaches of the High Atlas mountains, the highest range in North Africa (Djebel Toubkal – 4,167 m a.s.l.). Lobate features in the Irhzer Ikbi South at 3,800 m a.s.l. have been previously interpreted as an active rock glacier, but no measurements of ground or air temperatures are known to exist for the area. In order to assess on the possible presence of permafrost, analyse data from June 2015 to June 2016 fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Ground surface temperatures varied from − 4.5 to − 6 °C from December to March, under a continuous snow cover and are interpreted as a strong indicator of the probable presence of permafrost in the highest parts of the Toubkal Massif. Chardon and Riser (1981) suggested that an active rock glacier occurs close to this site, although Vieira et al (2017) did not support this interpretation because there is no steep front and no clearly defined debris body. However, Vieira et al (2017) did identify small lobate forms and arcuate ramparts in the talus, possibly indicating active periglacial dynamics, either by solifluction or permafrost creep.…”
Section: Toubkalmentioning
confidence: 92%
See 2 more Smart Citations
“…Ground surface temperatures varied from − 4.5 to − 6 °C from December to March, under a continuous snow cover and are interpreted as a strong indicator of the probable presence of permafrost in the highest parts of the Toubkal Massif. Chardon and Riser (1981) suggested that an active rock glacier occurs close to this site, although Vieira et al (2017) did not support this interpretation because there is no steep front and no clearly defined debris body. However, Vieira et al (2017) did identify small lobate forms and arcuate ramparts in the talus, possibly indicating active periglacial dynamics, either by solifluction or permafrost creep.…”
Section: Toubkalmentioning
confidence: 92%
“…However, no snow was observed in the Irhzher Ikhibi Nord (Fig. 11), Vieira et al (2017) found that over the period 2015-2016 ground surface temperatures were below 0 °C for the 6 months of the year from October to March, inclusive. Ground surface temperatures varied from − 4.5 to − 6 °C from December to March, under a continuous snow cover and are interpreted as a strong indicator of the probable presence of permafrost in the highest parts of the Toubkal Massif.…”
Section: Toubkalmentioning
confidence: 93%
See 1 more Smart Citation
“…It is possible that at one stage during glacial evolution, that they were debris-covered, but there is no residual morphological evidence to support this. Small rock glaciers are evident in the very highest cirques (Hughes 2018), although these are likely to be recent Holocene features (Vieira et al, 2017). Dresch (1941) also questioned the presence of moraines in the high cirques, including the highest boulder pile in the Irhzer Tamda (Dresch 1941, p. 599, Figure 197) and instead suggested that these are deposits formed by water torrents.…”
Section: Interpretation and Exposure Agesmentioning
confidence: 99%